Mathematical Thinking and Teaching Practice of School Teachers at Upper Primary Level - Prabhakar, Ashutosh; Gowramma, Ittira Poovaiah (INDIAN EDUCATIONAL REVIEW, 2022)
One of the goals of teaching mathematics is to develop mathematical thinking among students and to be able to identify, where mathematics is applicable in the real world. To inculcate mathematical thinking among students, it is necessary to involve mathematical thinking activities as a prominent part of their education. And if teachers are to encourage mathematical thinking in students, they need to engage in mathematical thinking throughout the lesson themselves. The crucial and essential part of the current scenario is knowing about teachers’ thinking towards their teaching practice. The effect of teachers’ mentality on improving the teaching process seems to be neglected to some extent. Considering this, existing gap, this study aims to go through teachers’ minds and find out how they think. A purposive sampling technique was used to select ten mathematics teachers teaching at upper primary level in five Kendriya Vidyalayas in Patna region. Open-ended questionnaires, rating scales and classroom observations were used to collect data, and analysed quantitatively and qualitatively to reveal the findings. Data formulation and thematic organisation were done through content analysis for further interpretation, which revealed that teachers with greater mathematical thinking skills employ more underlying mathematical processes and methods in their teaching such as analysing the subject matter, designing lessons for a specific goal, and understanding students’ reactions and responses.